Legislative analysis regarding the parallel trade of medicines - Erimia, Cristina-Luiza; Cazacincu, Radu-George (Technium BioChemMed, 2023)
Although the European Union has long faced the problem of the shortage of medicines, the European Parliament resolution of 17 September 2020 on the shortage of medicines [1] states that due to the increasing global demand for medicines and the COVID-19 pandemic, medicine shortages have become even more acute, affecting Member States' health systems and posing considerable risks to patients' health and care. The Committee on Industry, Research and Energy, in its opinion of 16.6.2020 [2], recognises that parallel trade can cause a shortage of medicines and calls on the Commission and the Member States to adequately address the problems of parallel trade in medicines in the EU, in order to prevent export shortages caused by considerable differences in the price of a medicine between Member States. In this context, this article aims to analyse the regulations at the level of the European Union, the case law of the Court of Justice of the European Union, as well as the national legislative measures relating to intra-EU trade on the pharmaceutical market.